The Influence of Influencer Credibility, Impulsive Buying, and Perceived Enjoyment on Social Commerce Impulse Buying of Food and Beverage Products - Bekti Setiadi; Nawiyah Nawiyah; Agung Widarman; M. Adik Rudiyanto; Iwan Henri Kusnadi; Arnold Sultantio Hutabarat (Institute of Advanced Knowledge and Science, 2026)
The purpose of this study is to analyze the effect of Influencer Credibility, Impulsive Buying and Perceived Enjoyment on Social Commerce Impulse Buying of food and beverage goods. The study was conducted quantitatively through the survey of respondents who purchased food and beverage goods through social commerce platforms. Data collection was conducted using online questionnaires with the purposive sampling method. The data was analyzed using multiple linear regression. The findings indicate that Influencer Credibility, Impulsive Buying, and Perceived Enjoyment have a partial and simultaneous positive and significant impact on Social Commerce Impulse Buying. The most important variable to affect Social Commerce Impulse Buying is Impulsive Buying. The results of the study show that the motives of impulse buying on social commerce platforms are affected by the credibility of influencers, impulsive behavior tendencies and the joyful purchasing experience. This research adds to the literature on digital marketing development, social commerce, and consumer behavior. It also provides practical implications for food and beverage businesses to develop better digital marketing strategies.